Perkembangan Model E-Business Marpoken Delivery di Kabupaten Mandailing Natal - Riski Wahdini; Windy Septia; Nurbaity (ADI Publisher, 2022)
Many problems occur in conducting business development, especiallyin businesses that use social media as a reference to promote andcarry out trading. This type of research is a qualitative approach, namelyusing the method of interviews and observations carried out by searching andcollect data related to Marpoken Delivery. Research purposesThis is to find out the development of the Marpoken Delivery e-Business Model in IndonesiaMandailing Natal Regency, especially during the Covid-19 pandemic. E-business modelused are B2B and B2C business models that can be carried out bybusiness people in cyberspace, especially Marpoken Delivery. Current pandemic conditionsThis makes online sales a solution for business people. One ofThe solution is to use E-Business as a way to earnprofit.